Hopes, Costs and Uneven Burden : The Impacts of Labor Influx from Road Projects on Women and Girls in Rural Malawi - World Bank (World Bank, Washington, DC, 2019)
This study attempts to explore the impacts of labor influx related to roads construction on poor rural communities in Malawi with particular attention to the impacts on girls and women.